Deep Tissue Massage and Nonsteroidal Anti-Inflammatory Drugs for Low Back Pain: A Prospective Randomized Trial - Majchrzycki, Marian (Hindawi Publishing Corporation, 2014)
Objective. To investigate whether chronic low back pain therapy with deep tissue massage (DTM) gives similar results to combined therapy consisting of DTM and non-steroid anti-inflammatory drugs (NSAID). Design. Prospective controlled randomized single blinded trial. Settings. Ambulatory care of rehabilitation. Participants. 59 patients, age 51.8 ± 9.0 years, with chronic low back pain. Interventions. 2 weeks of DTM in the treatment group (TG) versus 2 weeks of DTM combined with NSAID in the control group (CG). Main Outcome Measures. Visual analogue scale, Oswestry disability index (ODI), and Roland-Morris questionnaire (RM). Results. In both the TG and the CG, a significant pain reduction and function improvement were observed. VAS decreased from 58.3 ± 18.2 to 42.2 ± 21.1 (TG) and from 51.8 ± 18.8 to 30.6 ± 21.9 (CG). RM value decreased from 9.8 ± 5.1 to 6.4 ± 4.4 (TG), and from 9.3 ± 5.5 to 6.1 ± 4.6 (CG). ODI value decreased from 29.2 ± 17.3 to 21.4 ± 15.1 (TG) and from 21.4 ± 9.4 to 16.6 ± 9.4 (CG). All pre-post-treatment differences were significant; however, there was no significant difference between the TG and the CG. Conclusion. DTM had a positive effect on reducing pain in patients with chronic low back pain. Concurrent use of DTM and NSAID contributed to low back pain reduction in a similar degree that the DTM did.